Meios de Comunicação Social Portugueses (1974/2011) e os «Erros Médicos» - Lígia Gaspar Ernesto (Formifarma, LDA., 2012)
Objectives: (i) Qualitative and quantitative characterization of the presence of «medical errors» in not specialized Portuguese media. (ii) Comparison with official national reports on «medical errors». Methods: Qualitative and quantitative study including determination of frequencies. Electronic search was used to find news about «medical errors» that occurred in Portugal. Results: 210 cases that took place between 1974 and June 30, 2011 were analyzed. The number of cases of "medical errors" in the Portuguese media has been increasing, especially in the last decade. Doctors are the professional group most targeted in the news (64% of 309 professionals who were involved). In relation to patients, the highest frequency of cases was registered in the older age group (50), immediately followed by the youngest group (48). For institutions, the highest number of cases of "medical errors" was recorded in the hospitals (163). Among these, the Hospital of Santa Maria registered the highest number of cases (11). The most populous health regions registered the highest number of cases of "medical errors" in the press and also the highest number of complaints of health users in 2010. The medical areas with the highest number of cases were Urgency (47), Obstetrics (43) and Surgery (41). The most common situation in the media was the diagnostic error. We identified 42 condemnations for negligence, which occurred mainly after 2005. In the 33 cases where it was possible to identify the date of the event and the sentence, it was found that justice took an average of 7.8 years to make a decision. Conclusions: The results of this study are in agreement with data from official national reports on "medical errors". Further research is needed in this area, particularly in terms of the influence of media in forming opinions about the clinical safety of patients.